Control system migrations : a practical project management handbook - Roessler, Daniel (Momentum Press, 2013)
Reliable and effective control systems are a critical component of safe and profitable operations across process industries. And many of our industrial facilities today continue to operate using legacy control systems from the past four decades that are at or near the end of their lifecycles. Migration projects to modern control systems are complex, requiring detailed upfront planning, a methodical implementation strategy and astute project management.